Hubungan Tingkat Pengetahuan Pasien Hipertensi Terhadap Kepatuhan Minum Obat Antihipertensi di Klinik Herlina Cianjur: Relationship between the Knowledge Level of Hypertension Patients Regarding Compliance with Taking Antihypertensive Medication at the Herlina Cianjur Clinic - Viki Khoerunnisa; Linda Suryanti; Imam Syafi'i (UIMA Press, 2025)
Hypertension is still a health problem and is the main cause of death in developed and developing countries. According to data from (World Health Organization shows that around 1.13 billion people in the world experience hypertension. Treatment of hypertension with antihypertensive drugs is an important step to control blood pressure and prevent complications. However, patient compliance in taking antihypertensive medication is still a problem. The patient’s level of knowledge about hypertension and its treatment is one factor that can influence compliance with taking medication. Lack of knowledge often makes patients feel that they do not need to take medication regularly, especially if they do not experience symptoms. This study aimed to determine the relationship between the level of knowledge of hypertensive patients and compliance with taking antihypertensive medication at the Herlina Cianjur Clinic. The research method is quantitative with a cross-sectional design. The population in this study consisted of all individuals with hypertension at the Herlina Cianjur Clinic. The sampling technique was carried out using non-probability sampling, and 76 samples were obtained. The data used is primary data distributed through knowledge level questionnaires and medication adherence questionnaires. Data analysis was conducted using both univariate and bivariate methods, including the chi-square test. The results of the study showed that there was no relationship between the level of knowledge and adherence to taking antihypertensive medication, with p-value = 0.604 (p > 0.05).